2021
DOI: 10.3390/antibiotics10050471
|View full text |Cite|
|
Sign up to set email alerts
|

Alternatives to Antibiotics: A Symposium on the Challenges and Solutions for Animal Health and Production

Abstract: Antibiotics have improved the length and quality of life of people worldwide and have had an immeasurable influence on agricultural animal health and the efficiency of animal production over the last 60 years. The increased affordability of animal protein for a greater proportion of the global population, in which antibiotic use has played a crucial part, has resulted in a substantial improvement in human quality of life. However, these benefits have come with major unintended consequences, including antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 82 publications
0
40
0
Order By: Relevance
“…Diversified approaches based on nanoparticles, natural polysaccharides, bacteria, and phages have been reported as promising delivery vehicles for AMPs (23,24). Among these AMP delivery systems, B. subtilis has shown unique properties as an effective carrier for AMPs in previous studies with fish, mice, and swine (14,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Diversified approaches based on nanoparticles, natural polysaccharides, bacteria, and phages have been reported as promising delivery vehicles for AMPs (23,24). Among these AMP delivery systems, B. subtilis has shown unique properties as an effective carrier for AMPs in previous studies with fish, mice, and swine (14,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Although some review articles have suggested that the presence of TANs in the diet may negatively affect DMI in ruminants [ 1 , 9 , 57 ], in the present meta-analysis no changes in DMI were observed in response to dietary supplementation with TANs. This absence of changes in DMI probably occurred because the average dose of TANs used was 19.29 g kg −1 DM and negative effects of TANs on intake seem to occur with doses higher than 50 g kg −1 DM [ 4 , 9 , 12 ]. Similar to our results, two previously elaborated meta-analyses reported that dietary supplementation with TANs at average concentrations of 9.5 and 14.61 g kg −1 DM did not significantly affect DMI of dairy cows in production and beef cattle, respectively [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the inappropriate use of these products results in an accumulation of toxic residues in meat, which can affect the health of the consumer [ 2 , 3 ]. In addition, the emergence of bacterial strains resistant to the antibiotic effects [ 4 ] as well as the prohibition of these compounds in some countries [ 5 ] have led the industry and researchers to search for alternative products with similar effects as antibiotics, but of natural origin. Tannins (TANs), which are derived from plants, have received special attention and are among the most studied bioactive compounds, particularly in ruminants [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in several other literature reviews and articles [146][147][148][149][150][151][152][153][154], numerous other alternatives to antibiotics have also been explored, such as the addition of proteins, fibers, amino acids, enzymes, organic acids, essential oils, antimicrobial peptides, egg yolk antibodies, and spray-dried plasma to animal feed. Finally, it is interesting to note that several of these alternatives have also been explored for humans [146,147] and that research in animals and humans is mutually supportive.…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%